Recent achievements toward the development of Ni-based layered oxide cathodes for fast-charging Li-ion batteries. Issue 9 (9th February 2023) - Zhang, Yuxuan; Kim, Jae Chul; Song, Han Wook; Lee, Sunghwan
Abstract : This review enhances a fundamental understanding of the degradation mechanisms of Ni-based layered cathodes under fast-charging conditions from atomic to electrode scales. Design strategies for enhancing fast-charging performance are also suggested. Abstract : The driving mileage of electric vehicles (EVs) has been substantially improved in recent years with the adoption of Ni-based layered oxide materials as the battery cathode. The average charging period of EVs is still time-consuming, compared with the short refueling time of an internal combustion engine vehicle. With the guidance from the United States Department of Energy, the charging time of refilling 60% of the battery capacity should be less than 6 min for EVs, indicating that the corresponding charging rate for the cathode materials is to be greater than 6C. However, the sluggish kinetic conditions and insufficient thermal stability of the Ni-based layered oxide materials hinder further application in fast-charging operations. Most of the recent review articles regarding Ni-based layered oxide materials as cathodes for lithium-ion batteries (LIBs) only touch degradation mechanisms under slow charging conditions. Of note, the fading mechanisms of the cathode materials for fast-charging, of which the importance abruptly increases due to the development of electric vehicles, may be significantly different from those of slow charging conditions. There are a few review articles regarding fast-charging; however, their perspectives are limited mostly to battery thermal management simulations, lacking experimental validations such as microscale structure degradations of Ni-based layered oxide cathode materials. In this review, a general and fundamental definition of fast-charging is discussed at first, and then we summarize the rate capability required in EVs and the electrochemical and kinetic properties of Ni-based layered oxide cathode materials. Next, the degradation mechanisms of LIBs leveraging Ni-based cathodes under fast-charging operation are systematically discussed from the electrode scale to the particle scale and finally the atom scale (lattice oxygen-level investigation). Then, various strategies to achieve higher rate capability, such as optimizing the synthesis process of cathode particles, fabricating single-crystalline particles, employing electrolyte additives, doping foreign ions, coating protective layers, and engineering the cathode architecture, are detailed. All these strategies need to be considered to enhance the electrochemical performance of Ni-based oxide cathode materials under fast-charging conditions.